Note From the Editors - Chen, Jocelyn; Thornberg, Agnes (Consilience, 2021)
Dear Readers, We are proud to present Issue XXIV of Consilience: The Journal of Sustainable Development. As we approach the middle of 2021, we reflect on these past six months with a great sense of hope and optimism. The efficient vaccine distribution in the United States has brought back a feeling of normalcy as cases are dropping across the country. Although the COVID-19 pandemic is still very much real and full recovery from the tragedy that it has imposed will require a lot of time and resources, an end to the pandemic feels within reach and we are very inspired by the leadership and research that is paving the way. We recently passed the one-year anniversary of the murder of George Floyd, that sparked conversations and protests against racism across the globe. Racial inequality remains a deeply rooted problem in the United States and we are saddened to see that this spring brought with it further condemnable acts of hatred and violence towards individuals based on race and ethnicity. While we are very delighted to watch as the world has come together to eradicate the COVID-19 virus and distribute the vaccine, it has become clear that these systems are also characterized by inequality. The quest for sustainability is symbiotic with that of equity, we can therefore not look towards a sustainable future without addressing this issue as well. Although the end of the pandemic may be a time for celebration, we have greater challenges ahead of us. The climate crisis is gaining urgency for each day that passes and it is imperative that the world unites and works together to tackle it. In Issue XXIV, we selected a collection of articles that examine the state of the planet and climate change with scientific rigor and objectivity. We open the issue with innovative ideas of applying biofluorescent bacteria to solar concentrators and bamboo for climate change. Then, the issue dives into studies of the potential for Namibian youths in sustainable cooking and groundwater resources in Long Island and Shelter Island. Finally, we close the issue with an opinion piece evaluating renewable energy goals in the state of California. We are immensely proud of the work that has been put into this issue by our team of editors and the authors that have submitted to us. We encourage you to further engage with us and take a look at our Briefings column, which publishes shorter opinion pieces on hot-button topics. You can also subscribe to the Consilience pages on Facebook, Instagram, and Twitter to stay informed about new articles that are posted, author highlights, events, and other journal news. This spring also saw the launch of our very own newsletter that we invite you to subscribe to here. If you have any questions, comments, or concerns, please don't hesitate to contact us at consiliencejournal@gmail.com. We hope this issue has instilled you with the same feelings of hope and inspiration that we felt putting it together. Warmly, Agnes Thornberg, Editor-in-Chief Jocelyn Chen, Academic Journal Director